Crop Residue Effects on Nitrogen Mineralization, Microbial Biomass, and Rice Yield in Submerged Soils - Clément, A.; Chalifour, F.-P.; Ladha, J.K. (Wiley, 1995)
Urea, crop residues, and green manure are all suitable sources of N for lowland rice (Oryza sativa L.). However, N sources undergo mineralization at different rates, affecting rice N uptake and utilization. Little is known about the effect of the chemical composition of crop residues on N mineralization and rice performance. Two greenhouse experiments were conducted to determine the dynamics of N mineralization, microbial biomass, and rice N uptake. Twelve treatments representing a wide range of crop residue chemical composition and two controls (with and without urea) were compared. The N mineralization pattern ranged from rapid (Sesbania rostata Brem. and Oberm.) to immobilization at the beginning of the season (Cassia velosa L.). Immediately after incorporation, N mineralization was positively correlated to crop residue N concentration (r2 = 0.64, significant at P < 0.01), and negatively correlated to tannin concentration. However, at tillering, the tannin/N ratio was best correlated to the rate of N release (r2 = 0.86, significant at P < 0.01). Grain yield was best predicted by the (lignin + polyphenol)/N ratio (r2 = 0.67, significant at P < 0.01). Incorporation of residue into soil generally increased microbial biomass ninhydrin‐reactive N compared with control treatments at the tillering stage, but not at maturity. Microbial biomass N was highly correlated to soil NH+4‐N at rice tillering (r2 = 0.76, significant at P < 0.01). The N derived from fertilizer in rice was 35.4% on average for residue treatments, which was comparable with that of the urea control (33.5%). This study emphasizes the importance of considering the interactions among chemical constituents of crop residues to understand the dynamics of N release and uptake by rice.